2015
DOI: 10.1002/cne.23924
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the photoperiodic regulation of RF‐Amide related peptide (RFRP) and its receptor GPR147 in the syrian hamster

Abstract: RF-(Arg-Phe) related peptides (RFRP-1 and -3) are considered to play a role in the seasonal regulation of reproduction; however, the effect of the peptides depends on species and gender. This study aimed at comparing the RFRP system in male and female Syrian hamsters over long and short photoperiods to investigate the neuroanatomical basis of these differential effects. The neuroanatomical distribution of RFRP neurons and fibers, revealed using an antiserum recognizing RFRP-1 and -3, as well as GPR147 mRNA, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 53 publications
4
49
1
Order By: Relevance
“…Our finding of an orexigenic role of RFRP-3 in the jerboa is in agreement with previous results obtained in rats, mice, sheep and non-human primates21222324, but our data are the first to demonstrate that this metabolic effect might involve an increase in Npy and decrease in Pomc gene regulation. This finding is supported by earlier reports of the presence of the RFRP receptor and RFRP fiber terminals in the ARC of rodents84249 with some studies showing that RFRP terminals are in close apposition to NPY3050 and POMC30 neurons. However, studies investigating the effect of RFRP-3/GnIH on POMC and NPY neuronal activity reported paradoxical results since the peptide increased FOS protein in both NPY and POMC neurons in the sheep23, inhibited the firing rate of both POMC and NPY neurons in mice50 and increased Npy but not Pomc gene expression in the rat23 suggesting species-dependent hypothalamic targets of RFRP-3.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our finding of an orexigenic role of RFRP-3 in the jerboa is in agreement with previous results obtained in rats, mice, sheep and non-human primates21222324, but our data are the first to demonstrate that this metabolic effect might involve an increase in Npy and decrease in Pomc gene regulation. This finding is supported by earlier reports of the presence of the RFRP receptor and RFRP fiber terminals in the ARC of rodents84249 with some studies showing that RFRP terminals are in close apposition to NPY3050 and POMC30 neurons. However, studies investigating the effect of RFRP-3/GnIH on POMC and NPY neuronal activity reported paradoxical results since the peptide increased FOS protein in both NPY and POMC neurons in the sheep23, inhibited the firing rate of both POMC and NPY neurons in mice50 and increased Npy but not Pomc gene expression in the rat23 suggesting species-dependent hypothalamic targets of RFRP-3.…”
Section: Discussionsupporting
confidence: 88%
“…In the female jerboa, our study demonstrates that RFRP-3 induces activation of NPY and inhibition of POMC neurons resulting in a robust orexigenic effect. Even though Rfrp expression is inhibited by short days in seasonal species, including the jerboa14161931, and RFRP receptor expression is reduced in the ARC of short-day adapted hamsters42, we observed no difference in the effect of RFRP-3 on food intake in spring compared to autumn.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Previous studies claimed that Rfrp‐3 expression is inhibited by SP conditions and melatonin in hamsters (Henningsen, Poirel, et al, ; Rasri‐Klosen et al, ; Revel et al, ; Ubuka et al, ). Similarly, we also found a strong correlation between Rfrp‐3 and day length: a significant increase in Rfrp‐3 expression with increasing day length (from April to August) and a decline in Rfrp‐3 expression with the decreasing phase of day length (from August in October).…”
Section: Discussionmentioning
confidence: 95%
“…In mammals, this neuropeptide precursor cDNA encodes three peptides (also known as RFamide‐related peptides [RFRPs]), RFRP‐1, ‐2 and ‐3, in bovine and human (RFRP‐1 and ‐3 are LPXRFamide peptides, whereas RFRP‐2 is not). RFRP‐3 is now considered to be the mammalian orthologue of avian GnIH, although effects of RFRP‐1 on central and peripheral reproductive functioning have been reported, requiring further investigation to clarify the specific role of neuropeptide …”
Section: Discovery Of Gnih In Birdsmentioning
confidence: 99%